Personality correlates of dispositional forgiveness: a direct comparison of interpersonal and self-forgiveness using common transgression scenarios - Hampton, Lucas E.; Carruth, Nicholas P.; Lurquin, John H.; Miyake, Akira (Frontiers in Psychology, 2023)
Although the personality correlates of dispositional interpersonal forgiveness (forgiveness of others) have been well characterized, those of dispositional self-forgiveness are less well understood. Moreover, when the personality correlates are examined for both types of forgiveness, the comparison has been based on participants' self-report ratings on questionnaires.The current study sought to address these gaps in the literature by adopting a scenario-based approach, which has been used less frequently, especially in self-forgiveness research. A total of 160 participants read six fictional scenarios, each describing a severe transgression, from the perspective of the transgressor (self-forgiveness, n = 78) or the victim (interpersonal forgiveness, n = 82) of the transgression, and then responded to several items assessing different facets of forgiveness (avoidance, revenge, and benevolence). Participants' personality (Big Five) and explanatory style were also assessed.Consistent with prior literature, agreeableness and neuroticism generally predicted different facets of interpersonal forgiveness. These two personality traits also predicted facets of self-forgiveness, but, additionally, conscientiousness and one's tendency to internalize failure (the personal component of explanatory style) uniquely predicted self-forgiveness, especially avoidance motivations. These results point to both similarities and differences in the personality correlates for interpersonal and self-forgiveness. As a secondary, more exploratory aim, the current study compared the results from our scenario-based assessment of forgiveness to those based on a commonly used questionnaire, the Other and Self subscales of the Heartland Forgiveness Scale (HFS). As expected, the Other subscale of the HFS were associated with levels of interpersonal forgiveness assessed with our transgression scenarios, but, surprisingly, so were the HFS Self subscale. Moreover, the Self subscale was not associated with levels of self-Personality Correlates of Dispositional Forgiveness 3forgiveness assessed with transgression scenarios, except for avoidance motivations. These results suggest that scenario-based and questionnaire-based methods may capture different facts of forgiveness and cannot be used interchangeably, especially for the assessment of selfforgiveness. More generally, the current study illustrates the importance of conducting direct within-study comparisons of interpersonal and self-forgiveness as well as of different assessment methods to better understand the similarities and differences between the two types of forgiveness.